Evaluating VaR Forecasts under Stress – The German Experience - Stefan Jaschke; Gerhard Stahl; Richard Stehle (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
We present an analysis of VaR forecasts and P&L-series of all 13 German banks that used internal models for regulatory purposes in the year 2001. To this end, we introduce the notion of well-behaved forecast systems. Furthermore, we provide a series of statistical tools to perform our analyses. The results shed light on the forecast quality of VaR models of the individual banks, the regulator's portfolio as a whole, and the main ingredients of the computation of the regulatory capital required by the Basel rules.
urn:nbn:de:hebis:30-10376
Keywords: K23; G28; 330; banking supervision; VaR; exploratory data analysis; backtesting